1998
DOI: 10.1161/01.cir.98.7.719
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms of Atrial Contractile Dysfunction Caused by Sustained Atrial Tachycardia

Abstract: Background-Transient atrial contractile dysfunction ("atrial stunning") follows conversion of atrial fibrillation (AF) to sinus rhythm and has significant clinical implications; however, the underlying mechanisms are poorly understood. We investigated the hypothesis that rapid atrial activation (as during AF) impairs cellular contractility and affects cellular Ca 2ϩ handling. Methods and Results-Edge detection and indo 1 fluorescence techniques were used to measure unloaded cell shortening and intracellular Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(120 citation statements)
references
References 31 publications
2
115
0
3
Order By: Relevance
“…Maneuvers increasing intracellular calcium (pacing, isoproterenol, and calcium) improved atrial mechanical dysfunction, suggesting an actual or relative intracellular calcium deficiency to be responsible for the observed atrial mechanical dysfunction. Previous studies have demonstrated atrial arrhythmias to result in altered calcium handling 22 and intracellular calcium accumulation, 23 perhaps implicating a supranormal intracellular calcium level for the observed effects. However, evidence suggests that homeostatic mechanisms act to reduce the accumulating intracellular calcium by a decrease of the L-type calcium current.…”
Section: Implications For the Mechanism Of Atrial Mechanical Remodelimentioning
confidence: 94%
“…Maneuvers increasing intracellular calcium (pacing, isoproterenol, and calcium) improved atrial mechanical dysfunction, suggesting an actual or relative intracellular calcium deficiency to be responsible for the observed atrial mechanical dysfunction. Previous studies have demonstrated atrial arrhythmias to result in altered calcium handling 22 and intracellular calcium accumulation, 23 perhaps implicating a supranormal intracellular calcium level for the observed effects. However, evidence suggests that homeostatic mechanisms act to reduce the accumulating intracellular calcium by a decrease of the L-type calcium current.…”
Section: Implications For the Mechanism Of Atrial Mechanical Remodelimentioning
confidence: 94%
“…In addition to this 'tachycardiomyopathy' occurring at ventricular level, long-standing atrial fibrillation leads to a sort of atrial cardiomyopathy. This includes ultrastructural changes [24], an increase in atrial size [25], and a decrease in atrial contractility [26] that represent the anatomical and mechanical counterparts of the remodelling process, as well as a progressive depletion of atrial natriuretic peptide leading to an 'endocrinological silence' [27] It would appear logical to apply these general concepts suggesting a potentially detrimental role of atrial fibrillation to patients with heart failure, who have already a limited cardiac reserve and a reduced exercise tolerance. In contrast with these considerations, the impact of atrial fibrillation on mortality in patients with heart failure is controversial and, actually, most recent studies suggest that atrial fibrillation carries no independent risk.…”
Section: Clinical Rolementioning
confidence: 99%
“…5,6 Findings from these studies suggest a central role of calcium in atrial mechanical dysfunction associated with atrial arrhythmias with maneuvers increasing intracellular calcium observed to reverse atrial mechanical dysfunction. Others have reported altered cellular calcium handling 16 and intracellular calcium overload associated with atrial arrhythmias, 17 perhaps implicating a supranormal intracellular calcium level for the observed effects. However, evidence suggests that homeostatic mechanisms act to reduce the accumulating intracellular calcium by a decrease of the L-type calcium current.…”
Section: Implications For the Mechanisms Of Atrial Mechanical Remodelmentioning
confidence: 96%